Three medieval Greek romances : Velthandros and Chrysandza, Kallimachos and Chrysorroi, Livistros and Rodamni - Betts, Gavin, 1932-2013 (Routledge revivals, 2018)
These three 14th century medieval Greek romances, which are presented here for the first time in English translation, form part of a curious and previously neglected corner of literature.